Atypical Borrelia garinii infection in an immunocompromised patient mimicking high-grade lymphoma. (August 2022) - Eiferman, Victor; Guenno, Guillaume Le; Boiret-Dupré, Nathalie; Barres, Bertrand; Luciani, Léa; Fournier, Pierre Edouard
Highlights: Borrelia garinii belongs to the B burgdorferi complex Borrelia infections can be atypical in patients who are immunocompromised Borrelia serology is often negative in patients treated with rituximab Molecular biology is a valuable diagnostic tool in patients treated with rituximab Borrelia infection may be associated with various type of lymphoma Abstract: We report an atypical Borrelia garinii infection in a patient who was immunocompromised. It was first suspected as a transformation of follicular lymphoma into high-grade lymphoma. Spirochetes were directly observed on a peripheral blood smear and the diagnosis was confirmed using molecular methods. The clinical presentation and the diagnosis are unique and contrast with the cases described in the literature in patients who are immunocompromised.